Early Life Stress Influences Oxidative Stress Enzyme Activities in Liver, Heart, Kidney, Suprarenal Glands, and Pancreas in Male and Female Rat Pups - Bertha Fenton Navarro; Alexis Abraham Casimiro Aguayo; Yayr Luis Torres Gómez; Miguel Cervantes Alfaro; Luz Torner (MDPI AG, 2024)
Early life stress (ELS) is a risk factor for the development of chronic diseases resulting from functional alterations of organs in the cardiorespiratory and renal systems. This work studied the changes in oxidative stress enzyme activities (EAs) of SOD, CAT, GPX, GR, GST, NOS, MDA, and FRAP in different organs (heart, liver, kidney, adrenal glands (AGs), and pancreas) of male and female Sprague-Dawley rat pups on postnatal day (PN) 15, immediately after basal and acute or chronic stress conditions were accomplished, as follows: basal control (BC; undisturbed maternal pups care), stress control (SC; 3 h maternal separation on PN15), basal maternal separation (BMS; daily 3 h maternal separation on PN 1-14), and stress maternal separation (SMS; daily 3 h maternal separation on PN 1-14 and 3 h maternal separation on PN15). Acute or long-term stress resulted in overall oxidative stress, increase in EA, and reduced antioxidant capacity in these organs. Some different response patterns, due to precedent SMS, were observed in specific organs, especially in the AGs. Acute stress exposure increases the EA, but chronic stress generates a response in the antioxidant system in some of the organs studied and is damped in response to a further challenge.